2016
DOI: 10.1088/0253-6102/65/3/321
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Equivalence of Post-Newtonian Lagrangian and Hamiltonian Formulations

Abstract: It was claimed recently that a low order post-Newtonian (PN) Lagrangian formulation, which corresponds to the Euler-Lagrange equations up to an infinite PN order, can be identical to a PN Hamiltonian formulation at the infinite order from a theoretical point of view. This result is difficult to check because in most cases one does not know what both the Euler-Lagrange equations and the equivalent Hamiltonian are at the infinite order. However, no difficulty exists for a special 1PN Lagrangian formulation of re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The equivalence between both approaches was shown in Damour et al (2001), Damour et al (2002), de Andrade et al (2001) and Levi & Steinhoff (2014). However, different claims exist in , , Wang & Huang (2015), Chen & Wu (2016) and Huang et al (2016), stating that such differences are owed to the truncation of higher-order PN terms.…”
Section: Introductionmentioning
confidence: 97%
“…The equivalence between both approaches was shown in Damour et al (2001), Damour et al (2002), de Andrade et al (2001) and Levi & Steinhoff (2014). However, different claims exist in , , Wang & Huang (2015), Chen & Wu (2016) and Huang et al (2016), stating that such differences are owed to the truncation of higher-order PN terms.…”
Section: Introductionmentioning
confidence: 97%
“…3 Fortunately, another important result of [30] is that for a lower-order PN Lagrangian formulation with Euler-Lagrange equations to an infinite PN order there always exists a formally equivalent PN Hamiltonian at the infinite order from a theoretical point of view or a certain finite order from a numerical point of view. This result is supported analytically and numerically via a special 1PN Lagrangian formulation of a relativistic circular restricted three-body problem with the Euler-Lagrange equations and the equivalent Hamiltonian as a converging Taylor series [36]. Thus, the integrability or non-integrability of a PN Lagrangian formalism can be shown in terms of that of its formal equivalent PN Hamiltonian.…”
Section: Introductionmentioning
confidence: 73%
“…This strategy is extensively used in the PN Lagrangian of compact binaries [8][9][10][11][12][13], the equivalence analysis between the PN Hamiltonian and the PN Lagrangian approaches at the same order [14][15][16][17][18][19][20], and the dynamics of the PN circular restricted three-body problem [1,5,6]. Following this idea, the approximately truncated motion equations at the 1PN order for (13) are derived in [5] and expressed as…”
Section: Exact and Truncated Motion Equationsmentioning
confidence: 99%
“…During this procedure, truncation is a commonly used approach, which is conducted by substituting low-order equations of motion to high-order accelerations or by neglecting higher-order terms. This strategy is extensively used to investigate the dynamics of the PN Lagrangian compact binaries [8][9][10][11][12][13], the equivalence analysis between the PN Lagrangian and the PN Hamiltonian approaches [14][15][16][17][18][19][20], and the dynamics of the PN circular restricted three-body problem [1,5,6]. Among the discussion of the equivalence between the PN Lagrangian and the PN Hamiltonian approaches, the authors of [14][15][16]19] showed the physical equivalence of the two approaches at the same PN order.…”
Section: Introductionmentioning
confidence: 99%